FR2245875 (1978)
A shaft bearing retention means comprises a segmented ring having a conical inner surface which is placed about a large diameter shaft having a corresponding conical indentation about its periphery to receive the ring. The segments are retained in assembled position on the shaft by joining pins extended through interengaging lapped tongues on the ends of each segment and by attaching one or more flanged retaining rings thereto by screws or bolts. Additional clamping screws or bolts pass through the retaining ring and are threaded into the segments, projecting beyond the latter so as to bear against a thrust ring through which the shaft passes. The axially adjustable thrust ring engages a bearing assembly which is fixed against axial movement by a shoulder on the shaft. Axial force is produced against the bearing assembly by the clamping bolts due to wedging action of the mating conical surfaces on the shaft and the segmented ring.